Ketidakmampuan Membaca (Disleksia) dan Dampaknya Terhadap Perkembangan Anak - Fika Safitri; Faris Naufal Ali; Eva Latipah (WASIS : Jurnal Ilmiah Pendidikan, 2022)
The purpose of this study was to identify dyslexia disorders, and how to apply and treat them, so that they can help and reduce the impact of subsequent development. This research uses library research and the type of research is descriptive qualitative analysis. The data collection method is from the book "Innovations in Educational Psychology" by David Preiss and Robert J. Sternberg, as the main source (primary) and a review of other literatures that discuss the same research as this study as a second (secondary) source, to explore further opinions or views on dyslexia and its impact on development. The results of the study, dyslexia is one type of learning difficulty in children in the form of a reading disability, a symptom that is not caused by the ability of sight, hearing, intelligence, or language skills, but a disturbance in the brain's processing when receiving an information processing. Eye movement control, visual perception, understanding of orthographic, phonological, and semantic features of words, higher-order language and cognitive, storage, and concentration skills are all necessary for reading.